Prolonged Ex vivo expansion and differentiation of naïve murine CD43(-) B splenocytes - Zambrano, Kenny; Jerome, Valerie; Freitag, Ruth; Buchholz, Rainer; Jäck, Hans-Martin; Hübner, Holger; Schuh, Wolfgang; Buchholz, Rainer (Biotechnology Progress, 2016)
Ex vivo expansion of naive primary B cells is still a challenge, yet would open new possibilities for in vitro studies of the immune response or the production of monoclonal antibodies. In our hands, unstimulated murine B cells did not expand in significant numbers, while culture viability decreased rapidly within a few days. Activation mimicking in vivo stimulation through either T cell-independent or T-cell dependent signaling, led to several division cycles, albeit accompanied by irreversible differentiation. By co-culturing B cells under moderate hypothermia (30°C) on live feeder fibroblasts expressing recombinant CD40 ligand (CD154) and by repeatedly transferring cultured B cells to new feeder cell cultures, we could extend the growth of primary mouse B cells compared to cultures maintained at 37°C. B cells under these conditions showed an activated phenotype as shown by the presence of AID and IRF4, two factors required for IgH class switch recombination in antigen-activated B cells. In contrast to cells cultured at 37°C, B cells under hyperthermia did surprisingly not differentiate into Blimp-1 expressing plasmablasts. Thus, the repeated batch process under hyperthermic conditions represents a first step towards the development of a continuous cultivation system for the expansion of primary B cells. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:978-989, 2016.
EVALuna2:13639